The Implementation of Waterfall Method in the Development of Accounting Information Systems for Web-Based Savings and Loans Data Processing: Case study: Sompak Awe Jaya cooperative - Nanda Diaz Arizona; Yulia Yulia (Indonesian Scientific Journal, 2022)
The Sompak Awe Jaya Cooperative currently manages conventional data, namely recording every savings and loan transaction in a ledger, which is then summarized in Microsoft Excel. Calculations for financial transactions use a calculator, so it takes a long time to process them. So the authors are interested in designing a savings and loan information system at the Sompak Awe Jaya cooperative. The idea of this design is that the finance department can efficiently process savings and loan data, automatic financial calculations are carried out by the system, and membership registration through the application will increase work efficiency. Meanwhile, cooperative managers can track savings and loan activities, view financial transaction data, receive reports, and print existing reports and this system is accessed by two actors, namely admin and finance. Therefore the author aims to create an accounting information system for processing savings and loans so that data management is carried out efficiently and effectively and helps secure existing data because the data is stored in the database. This design uses entity relationship diagram modeling and logical record structure for database design while modeling system flow using user case diagrams, deployment diagrams, activity diagrams, and sequence diagrams.